PARADOX OF POVERTY IN VILLAGE Ubud - Sudipa, I Nyoman (E-Journal of Cultural Studies; Volume 7, Number 3, Agustus 2014, 2014)
The research raises poverty as a social reality in the middle of the sparkling tourism in Ubud Village . This study focused on the discussion : ( 1 ) why is there poverty , ( 2 ) what efforts the government and other agencies to reduce poverty , and ( 3 ) how the effects of poverty are emerging . This study used qualitative methods . Data obtained through observation , interviews , and documentation . The results showed , poverty in the village of Ubud , which is caused by external factors such as government policy reference data, which is not clear , the lack of proper diagnosis , addressing poverty is not integrated and overlapping , and the failure of tourism development policies . External factors supported internal factors , namely the economic constraints , resources , and socio-cultural pressures , lifestyle , consumer behavior , asset ownership , land , and the cost of customs and rituals . Government efforts made ??through the program financially and non- financially poverty reduction through policy or regulation , mentoring , and training . NGOs make efforts to non - financially as a companion , mediator , facilitator and prepare sosial.Dampak mapping poverty in the village of Ubud is to reduce public confidence in the government , social conflict , and economic conflicts . The impact on tourism is tourism failing to provide social welfare . The impact for the community is resulting in social inequality , conflict , rising crime , and the inheritance of poverty
Keywords: poverty; tourism; government policy